Effects of MAPE and EB irradiation techniques on the mechanical properties of crosslinked rubber toughened nanocomposites - Jamal, Nur Ayuni; Anuar, Hazleen; Abd Razak, Shamsul Bahri (Malaysian Rubber Board, Malaysia, 2011)
Improving the mechanical properties of high density polyethylene (HDPE)/ethylene propylene diene monomer (EPDM) matrix is the main target of developing HDPE/EPDM filled organophilic montmorillonite (OMMT). Both HDPE/EPDM matrix and HDPE/EPDM filled OMMT were first prepared via intercalation technique at different OMMT loadings. Two types of crosslinking techniques were applied namely, maleic anhydride polyethylene (MAPE) and electron beam (EB) irradiated systems. The effectiveness of MAPE and EB irradiation crosslinkings were then compared with control and analysed based on the mechanical tests and morphological examination. The mechanical tests revealed that control, MAPE and EB irradiated systems had attained the optimum mechanical properties at 4 vol% OMMT content. EB irradiation absorbed dose of 100 kGy showed excellent mechanical properties with higher crosslinking degree is proved by gel content analysis. X-ray diffraction (XRD) analysis confirmed the existence of delamination of OMMT by MAPE and EB irradiation techniques based on disappearance of the characteristic peak. The degree of delamination was further investigated by transmission electron microscope (TEM).